Circadian rhythms in glucose and lipid metabolism in nocturnal and diurnal mammals. (15th December 2015) - Kumar Jha, Pawan; Challet, Etienne; Kalsbeek, Andries
Abstract: Most aspects of energy metabolism display clear variations during day and night. This daily rhythmicity of metabolic functions, including hormone release, is governed by a circadian system that consists of the master clock in the suprachiasmatic nuclei of the hypothalamus (SCN) and many secondary clocks in the brain and peripheral organs. The SCN control peripheral timing via the autonomic and neuroendocrine system, as well as via behavioral outputs. The sleep–wake cycle, the feeding/fasting rhythm and most hormonal rhythms, including that of leptin, ghrelin and glucocorticoids, usually show an opposite phase (relative to the light–dark cycle) in diurnal and nocturnal species. By contrast, the SCN clock is most active at the same astronomical times in these two categories of mammals. Moreover, in both species, pineal melatonin is secreted only at night. In this review we describe the current knowledge on the regulation of glucose and lipid metabolism by central and peripheral clock mechanisms. Most experimental knowledge comes from studies in nocturnal laboratory rodents. Nevertheless, we will also mention some relevant findings in diurnal mammals, including humans. It will become clear that as a consequence of the tight connections between the circadian clock system and energy metabolism, circadian clock impairments (e.g., mutations or knock-out of clock genes) and circadian clock misalignments (such as during shift work and chronic jet-lag) have an adverse effect on energy metabolism, that may trigger or enhancing obese and diabetic symptoms. Highlights: The central pacemaker shows its peak activity at the same astronomical time in diurnal and nocturnal species. Circadian clocks regulate the daily rhythmicity of glucose and lipid metabolism. Daily rhythms of metabolic processes and hormonal release are oppositely phased in nocturnal and diurnal mammals. Various disturbances in the metabolic phenotype have been reported in clock gene mutant and knock-out mice. Evidence for a causative link between circadian desynchronization and metabolic abnormalities is accumulating.